A Review of the Impact of Preoperative Chemoradiotherapy on Outcome and Postoperative Complications in Esophageal Cancer Patients. (August 2015) - Wilke, Trevor J.; Bhirud, Abhijeet R.; Lin, Chi
Abstract : Preoperative chemoradiotherapy has emerged in the treatment of esophageal cancer as a means to down-stage tumors, improve local control, and possibly improve overall survival. However, there are concerns that postoperative complications may be increased by preoperative chemoradiotherapy. We review the rationale for preoperative chemoradiotherapy. We review the literature to identify the potential postoperative complications, the risk of complications, and the risk factors for complications. Although individual and previous studies have shown an increased risk of postoperative complications, the 4 most recent randomized trials published after the year 2000 have not shown an increase in postoperative complications and mortality rates in patients treated with preoperative chemoradiation compared with patients treated with surgery alone. Pulmonary complications are frequently reported, and we focus on dosimetric factors that can be used to minimize lung toxicity. Several dose-volume-histogram parameters, including V10≥40%, V15≥30%, V20≥20%, have been shown to correlate with 32% to 35% of pulmonary complications including pneumonia and acute respiratory distress syndrome. More recent evidence has suggested that an absolute volume of lung spared doses of > 5 Gy (VS5) correlates with pulmonary complications. As these data show, low-dose volume may be more important in the prevention of pulmonary complications than high-dose volume. These dosimetric constraints can be used by physicians to prevent postoperative pulmonary complications in patients treated with preoperative chemoradiotherapy.